Pengaruh Jalur Rel Kereta Api pada Nilai Tanah di Sekitarnya (Studi Kasus pada Jalur Rel Kereta Api di Kota Surakarta) - , Joko Susanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The presence of railroad lines provide a separate impacts for the surrounding community, not least to give effect also to land value. Society as a third party who owns the land around the railroad get negative externalities from the existence of a railroad train. Researchers have suspected that the closer a property land in the city of Surakarta from the railroad, the value will increasingly come down. This study aims to analyze the influence of railroad track on the surrounding land value in the area of the city of Surakarta. This study uses cross section data, 84 vacant land transactions in 2010 -2011. In addition, this study also aims to analyze the influence of land area, the land distance from the CBD , the land distance from the nearest railway station, dummy land rectangular shape irregular, and dummy commercial/tradding area. Analysis tool in the form of multiple regression analysis with double-log model (log-log) to achieve the purposes of research. The results showed that the variable land distance from the railway and dummy of commercial/tradding areas give positive and significant influence on land value. Variable land area has positive influence on land values but not significant. Variable land distance from the CBD, and variable land distance from the nearest railway station gives a negative and significant impact on the value of land in the city of Surakarta. Meanwhile dummy land rectangular shape irregular puts a negative but insignificant effect on the value of the land. So, researchers hypothesized that investigators suspected that the presence of the railroad gave negative externalities so that the lower value of land around it proved. The closer the location of the land in Surakarta with railway lines, the value will increasingly come down.